2004
DOI: 10.1038/nature02647
|View full text |Cite
|
Sign up to set email alerts
|

An SCF-like ubiquitin ligase complex that controls presynaptic differentiation

Abstract: During synapse formation, specialized subcellular structures develop at synaptic junctions in a tightly regulated fashion. Cross-signalling initiated by ephrins, Wnts and transforming growth factor-beta family members between presynaptic and postsynaptic termini are proposed to govern synapse formation. It is not well understood how multiple signals are integrated and regulated by developing synaptic termini to control synaptic differentiation. Here we report the identification of FSN-1, a novel F-box protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
241
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(252 citation statements)
references
References 28 publications
11
241
0
Order By: Relevance
“…In C. elegans, FSN-1 is required for the restriction and/or maturation of synapses in presynaptic neurons, and SCD-2 may serve as a downstream target for FSN-1 to stabilize the synaptic formation [43] . The amount and localization of SCD-2 are negatively regulated by FSN-1, and mutation of scd-2 suppresses the synaptic defects of fsn-1 [43] . Interestingly, we found that the sensory integration defects of fsn-1 mutants were obviously inhibited by scd-2 mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In C. elegans, FSN-1 is required for the restriction and/or maturation of synapses in presynaptic neurons, and SCD-2 may serve as a downstream target for FSN-1 to stabilize the synaptic formation [43] . The amount and localization of SCD-2 are negatively regulated by FSN-1, and mutation of scd-2 suppresses the synaptic defects of fsn-1 [43] . Interestingly, we found that the sensory integration defects of fsn-1 mutants were obviously inhibited by scd-2 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…7B, C). It has been indicated that fsn-1 mutants have a slightly reduced body length and normal locomotion [43] . Here it was further demonstrated that both fsn-1 and scd-2 mutants showed a normal phenotype of locomotion behavior as revealed by body bend (Fig.…”
Section: A F-box Protein Fsn-1 and Its Target Scd-2 Regu-mentioning
confidence: 99%
“…And this neuron-specific, SCF-like complex provides a localized signal to attenuate presynaptic differentiation [22] . Suppressor of Constitutive Dauer formation (SCD-2) may be a target or a downstream effector by which FSN-1 stabilizes synaptic formation [22] .…”
Section: Genetic Interactions Of Unc-64 and Ric-4 With Insulinmentioning
confidence: 99%
“…Suppressor of Constitutive Dauer formation (SCD-2) may be a target or a downstream effector by which FSN-1 stabilizes synaptic formation [22] . Furthermore, RPM-1 negatively regulates a p38 MAP kinase pathway composed of the dual leucine zipper-bearing MAPKKK DLK-1, the MAPKK MKK-4, and the p38 MAP kinase PMK-3 [23] .…”
Section: Genetic Interactions Of Unc-64 and Ric-4 With Insulinmentioning
confidence: 99%
“…[1][2][3][4][5][6] Previous studies have shown that in contrast to other F-box proteins that assemble SCF ubiquitin ligase complexes, Fbxo45 forms an atypical ubiquitin ligase complex that contains Skp1 and the Ring-finger protein PAM (protein-associated with myc) also known as MYCBP2 (mycbinding protein 2). 7,8 Fbxo45 has been linked to the proteasomal degradation of a few targets including p73 9 and Munc13-1. 10 Fbxo45 is one of only six F-box proteins that are conserved in metazoans and the only F-box protein known to contain a SPRY domain, 3 which was first identified as a sequence repeat in the dual-specificity kinase splA and ryanodine receptors.…”
mentioning
confidence: 99%